Strategi Pemasaran Dan Pengelolaan Sumber Daya Manusia Terhadap Keberhasilan Usaha Yang Dimediasi Omset Penjualan Pada Pengusaha Fried Chicken Sabana Di Cikarang Timur - Sibagariang, Devi; Mulyono, Joko (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In the context of a business era that continues to develop, one sector that continues to exist and is promising in the future is the culinary industry, especially the fast food business which has become the choice of consumers in their daily meals. The presence of a practical and fast food menu is the main attraction, making the culinary industry an attractive investment for PT business players. Sumber Berkah Niaga, in principle, companies are generally able to plan, implement and launch their business activities from time to time in order to maintain and improve the quality of their products and operations as well as achieve innovation to continue to maintain the company's existing working position nationally. Currently there are more than 2,000 commercial branches. The research that the author will use uses quantitative methods. Quantitative research methods can be interpreted as research methods that are based on the philosophy of positivism, used for research on certain populations or samples, collecting data with research instruments, analyzing statistical data, by testing hypotheses that have been determined. The respondent in this research is the owner of the Savana outlet. fried chicken for 100 people. This is in accordance with the sampling method used in this research, namely the simple random sampling technique and calculating saturated samples, where the entire population is sampled. Based on the amount of data obtained, namely with a population of 100 owners, the number of samples taken was also 100 respondents. The coefficient of the t-statistic parameter for the Marketing Strategy (X1) - Sales Turnover (Z) variable has a value of 4.727 so it is declared significant.